Endothelial Cell Redox Regulation of Ischemic Angiogenesis. Issue 6 (June 2016) - Cohen, Richard A.; Murdoch, Colin E.; Watanabe, Yosuke; Bolotina, Victoria M.; Evangelista, Alicia M.; Haeussler, Dagmar J.; Smith, Melissa D.; Mei, Yu; Tong, XiaoYong; Han, Jingyan; Behring, Jessica B.; Bachschmid, Markus M.; et al.
Abstract : Abstract: The endothelium produces and responds to reactive oxygen and nitrogen species (RONS), providing important redox regulation to the cardiovascular system in physiology and disease. In no other situation are RONS more critical than in the response to tissue ischemia. Here, tissue healing requires growth factor–mediated angiogenesis that is in part dependent on low levels of RONS, which paradoxically must overcome the damaging effects of high levels of RONS generated as a result of ischemia. Although the generation of endothelial cell RONS in hypoxia/reoxygenation is acknowledged, the mechanism for their role in angiogenesis is still poorly understood. During ischemia, the major low molecular weight thiol glutathione (GSH) reacts with RONS and protein cysteines, producing GSH-protein adducts. Recent data indicate that GSH adducts on certain proteins are essential to growth factor responses in endothelial cells. Genetic deletion of the enzyme glutaredoxin-1, which selectively removes GSH protein adducts, improves, whereas its overexpression impairs revascularization of the ischemic hindlimb of mice. Ischemia-induced GSH adducts on specific cysteine residues of several proteins, including p65 NF-kB and the sarcoplasmic reticulum calcium ATPase 2, evidently promote ischemic angiogenesis. Identifying the specific proteins in the redox response to ischemia has provided therapeutic opportunities to improve clinical outcomes of ischemia.